Thermodynamics and kinetics of thermal inactivation of peroxidase from mangosteen (Garcinia mangotana L.) pericarp - Deylami, Mahsa Ziabakhsh; Abdul Rahman, Russly; Tan, Chin Ping; Bakar, Jamilah; Olusegun, Lasekan (School of Engineering, Taylor’s University College, 2014)
Mangosteen(Garcinia mangostana L.) pericarp is an abundant source of phytochemicals. Blanching prior to further process stabilizes these valuable compounds. In this research, crude peroxidase (POD) was extracted from mangosteen peel using Triton X6100. Kinetics of POD inactivation was studied over temperature range of 606 100°C. The inactivation kinetics followed a monophasic first6order model with k values between 1.93×10626 8.14×1062 min 61. The decreasing trend of k values with increasing temperature indicates a faster inactivation of peroxidase from mangosteen pericarp at higher temperatures. The activation energy (Ea) of 35.06 kJ/mol was calculated from the slope of Arrhenius plot. Thermodynamic parameters (Mangosteen (Garcinia mangostana L.) pericarp is an abundant source of phytochemicals. Blanching prior to further process stabilizes these valuable compounds. In this research, crude peroxidase (POD) was extracted from mangosteen peel using Triton X6100. Kinetics of POD inactivation was studied over temperature range of 606 100°C. The inactivation kinetics followed a monophasic first6order model with k values between 1.93×10626 8.14×1062 min 61. The decreasing trend of k values with increasing temperature indicates a faster inactivation of peroxidase from mangosteen pericarp at higher temperatures. The activation energy (Ea) of 35.06 kJ/mol was calculated from the slope of Arrhenius plot. Thermodynamic parameters (∆H, ∆G, ∆S) for inactivation of peroxidase at different temperatures (606100°C) were studied in detail. The results of this research will help to design pre6processing conditions of mangosteen pericarp as a source of antioxidants.